P312 A French Project Of Interregional And Shared Guidelines In Supportive Care. (15th August 2013) - Farsi, F; Klein, I; Jovenin, N; Labrosse, H; Brunet, M; Block, V; Krakowski, I
Abstract : Background: In France, access to supportive care is a right for cancer patients It is enshrined in the health regulations (1st and 2nd national cancer plans). But equity in this access is still evolving. In this context a national learned society and the regional oncology networks are desired to support professionals by organising the sharing and exchanges on the decision support tools Objectives: Gradually enlist all French regional cancer networks and all French experts in selecting the priority thematic, methodological support in the working groups and in objectives of implementation involve the maximum of professionals in the re-reading and validation of shared guidelines Method: Establishment of a national committee dedicated to supporting methodological and organisational project. - Needs analysis and choice of themes by regional cancer networks - recruitment of experts by both the networks and the learned societies - establishment of inter-disciplinary working group - organisation of a re-reading solicitant learned society and cancer networks - National Day (J2R) with dedicated workshops and plenary sessions to confirm or update the guidelines. Results and Conclusion: After 4 years, this project with regional networks complete 30 different shared guidelines and the attended by professionals of all the French regions (oncologist; surgeons, supportive care specialists, nurses).